Pendidikan Akhlak Menurut Imam Al Ghazali - Abdul Natsir; Mishbahush Shudur; Tri Harmono (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
ABSTRACT This research aims to comprehend how moral education is understood by Imam Al-Ghazali and to identify the methods employed by Imam Al-Ghazali in moral education. This research employs a qualitative approach, utilizing a content analysis method and the Library Research method. Data collection techniques include reading the book Ihya Ulumiddin Volume III by Abu Hamid Al-Ghazali regarding methods of moral education (as primary data), collecting and tracing translations of Ihya Ulumiddin (The Revival of the Religious Sciences), Ya Ayyuhal Walad (O My Beloved Son), and Al-Munqizu Minad-Dhalal (Deliverance from Error) by Abu Hamid Al-Ghazali, as well as studying, reviewing, and understanding analyses found in books that serve as secondary data sources. The results of this study show that the methods used by Imam Al-Ghazali in moral education are highly diverse, including the lecture method, discussion and question-and-answer methods, storytelling method, assignment method, mujahadah and riyadhah methods, as well as the method of giving rewards and punishments. Keywords : Moral Education, Imam Al-Ghazali